Analisis Prediksi Pasang Surut Air Laut Di Perairan Makassar Dengan Metode Admiralty - Rizky, Indah Aulia; Hendri, Andy; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This research aims to determine the beginning of the observation time that produces the most accurate prediction data. The pasut prediction method used is admiralty method with 15 days observation data as much as 115 variations of data, then simulation data will be verified against the simulation data. Based on the results of the analysis of root mean square error (RMSE) value for each initial variation of the observation time, then the beginning of the most accurate observation time based on the smallest error value is obtained at 29.47 cm on the 15 hijri ladder (full moon phase). Nilai Formzahl average obtained 2.11 so that the type of pasut at the location of this study is skewed daily (Mixed tide prevailing diurnal). The results of the correlation coefficient analysis (r) of each variation of the initial time of observation show that the highest correlation value is on the 16th of Hijriah of 0.43, meaning that it has a moderate correlation. Keywords: beginning of time, admiralty method, correlation, formzahl, hijri